2021
DOI: 10.1007/s00134-021-06581-1
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive respiratory support following extubation in critically ill adults: a systematic review and network meta-analysis

Abstract: Purpose: Systematic review and network meta-analysis to investigate the efficacy of noninvasive respiratory strategies, including noninvasive positive pressure ventilation (NIPPV) and high-flow nasal cannula (HFNC), in reducing extubation failure among critically ill adults. Methods:We searched databases from inception through October 2021 for randomized controlled trials (RCTs) evaluating noninvasive respiratory support therapies (NIPPV, HFNC, conventional oxygen therapy, or a combination of these) following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 76 publications
1
30
0
Order By: Relevance
“…Although recent advances in critical care technology have significantly improved the prognosis and survival of patients receiving ventilator support ( 26 ), extubation failure still occurs in approximately 10–15% of patients ( 27 ). Previous studies have shown that extubation failure may be associated with higher rates of tracheotomies, increased mortality, prolonged stay in the intensive care unit, and impaired functional outcome after recovery ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although recent advances in critical care technology have significantly improved the prognosis and survival of patients receiving ventilator support ( 26 ), extubation failure still occurs in approximately 10–15% of patients ( 27 ). Previous studies have shown that extubation failure may be associated with higher rates of tracheotomies, increased mortality, prolonged stay in the intensive care unit, and impaired functional outcome after recovery ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and network meta-analysis including 36 RCTs in adults showed a lower reintubation rate with noninvasive respiratory support compared with usual care, although no mode of noninvasive respiratory support proved superior ( 72 ). In pediatrics, there is very little data supporting or refuting the use of noninvasive ventilation to prevent reintubation ( 73 , 74 ).…”
Section: Use Of Niv After Extubationmentioning
confidence: 99%
“…The use of high-flow nasal cannula (HFNC) in critical care areas has increased over the past few years, particularly during the COVID-19 pandemic [ 1 ]. HFNC has been shown to effectively reduce intubation rates for patients with acute hypoxemic respiratory failure (AHRF) [ 2 ] and prevent post-extubation respiratory failure [ 3 ]. It may also be non-inferior to noninvasive ventilation to prevent reintubation for patients with chronic obstructive pulmonary disease (COPD) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%